Perylene diimide oligomer nanoparticles with ultrahigh photothermal conversion efficiency for cancer theranostics - Gong, Qiuyu (2021)
Developing one agent that has reasonable stability and ultrahigh photothermal conversion efficiency (PTCE) for near-infrared (NIR) photothermal cancer treatment remains a great challenge, but is highly desirable. In this research, we developed a perylene diimide (PDI)-based oligomer (OPDI) through coupling monomeric PDI derivatives together. OPDI exhibited slightly red-shifted absorption at NIR region compared with monomeric PDI. More importantly, the self-assembled OPDI nanoparticles not only exhibited high stability and preferable biocompatibility, but also possessed an ultrahigh PTCE (up to 79.8%, higher than many other photothermal agents reported before). This OPDI photothermal agent has been demonstrated to exhibit excellent therapeutic effects. Our research provides a guide for the exploitation of photothermal agents with ultrahigh PTCE.